2002
DOI: 10.1109/jproc.2002.804680
|View full text |Cite
|
Sign up to set email alerts
|

Rapid development of nucleic acid diagnostics

Abstract: There has been a significant increase, fueled by technologies from the human genome project, in the availability of nucleic acid sequence information for viruses and bacteria. This paper presents a computer-assisted process that begins with nucleic acid sequence information and produces highly specific pathogen signatures. When combined with instrumentation using the polymerase chain reaction, the resulting diagnostics are both specific and sensitive. The computational and engineering aspects of converting raw… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
31
0

Year Published

2004
2004
2009
2009

Publication Types

Select...
4
3
2

Relationship

0
9

Authors

Journals

citations
Cited by 39 publications
(31 citation statements)
references
References 21 publications
0
31
0
Order By: Relevance
“…Analytical specificity of the END RRT-PCR, determined by a combination of computer-based and benchlevel screening of primers and probes, 6 demonstrated no false-positive reactions. Evaluation of clinical case material additionally indicated that the assay did not cross-react with Mycoplasma spp., avian influenza virus, avian infectious bronchitis virus, avian laryngotracheitis vaccine strain, or near neighbor APMV-1 or PPMV-1 viruses, including a unique PPMV-1 detected during the outbreak (GenBank accession AY428960).…”
Section: Resultsmentioning
confidence: 99%
“…Analytical specificity of the END RRT-PCR, determined by a combination of computer-based and benchlevel screening of primers and probes, 6 demonstrated no false-positive reactions. Evaluation of clinical case material additionally indicated that the assay did not cross-react with Mycoplasma spp., avian influenza virus, avian infectious bronchitis virus, avian laryngotracheitis vaccine strain, or near neighbor APMV-1 or PPMV-1 viruses, including a unique PPMV-1 detected during the outbreak (GenBank accession AY428960).…”
Section: Resultsmentioning
confidence: 99%
“…Multiple layers of in silico mining and in vitro selection processes can be combined using high throughput wet chemistry evaluation to create a discovery pipeline for microbial signature sequences. In this way, many of the same informational tools developed for use in the Human Genome Project can also be marshaled to feed a discovery pipeline leading to new molecular diagnostics for bacteria and viruses (94).…”
Section: High-throughput Methods For Reagent Discoverymentioning
confidence: 99%
“…PNNL's SWIR CRDS instrument is outfitted with a cavity that has a volume of 490 cm 3 . If it is assumed that a sampling apparatus could be designed such that all gas phase products from biological agent pyrolysis would be swept into a prior evacuated CRDS cavity, then the amount of pyrrole and pyridine that needs to come from pyrolysis in order to be detected is 1.47 x 10 15 and 7.35 x 10 15 molecules, respectively.…”
Section: Swir Crds Feasibility For Detection Biological Agent Pyrolysmentioning
confidence: 99%